LITERATURE REVIEW : THE APPLICATION OF SOAK FEET WARM WATER THERAPY ON DECREASE BLOOD PREASSURE IN ELDERLY WITH HYPERTENSION - Laila Tafricha Sari; Yeni Yuliastanti; Heni Yuniarti (Midwifery and Nursing Research, 2021)
Background : Hypertension is a silent killer because it is a disease that does not show typical symptoms. Based on reports worldwide, an estimated 17,7 million people die of herat desease and blood vessel disease by 2025, hypertension suffers are estimated to reach 1,6 billion people (WHO, 2013). Management of hypertension is more focused on pharmacological techniques and Non-pharmacological techniques.  Non-pharmacological techniques that can be used are soak feet warm water therapy in people with elderly hypertension.Purpose : To provide a theoretical basis for research on non-pharmacological soak feet warm water therapy in elderly with hipertension sufferers.Methods : This study uses a literature review method, the databases used are Google Scholar, PubMed, and Garba Rujukan Digital with a time limit of the last 5 years. Results : The application of soak feet warm water therapy in elderly with hypertension sufferers has a significant effect on reducing blood preassure.Conclusion : Giving soak feet warm water therapy has an effect on reducing blood preassure in people with elderly with hypertension Keywords : hypertension, elderly, soak feet warm water therapy1Student Departement of Ners Polytechnic Health Ministry of SemarangJl. Perintis Kemerdekaan, Magelang Utara, Kota Magelang, Jawa Tengah, Indonesia2Lecturer Departement of Polytechnic Health Ministry of SemarangJl. Perintis Kemerdekaan, Magelang Utara, Kota Magelang, Jawa Tengah, Indonesia3Public Health Office of Magelang CityJl. Jend. Sarwo Edhie Wibowo No.2, Kota Magelang, Jawa Tengah, Indonesia